Exploring and collecting perennial forage and grain legume crop genetic diversity in Voronezh and Tambov provinces (Results of the collecting mission, 2016) - L. L. Malyshev; V. F. Chapurin; T. V. Buravtseva (Труды по прикладной ботанике, генетике и селекции)
Surveying vegetation in various areas within Russia is an important link to successful management of plant genetic resources. Species and forms of wild perennial legumes and forage grasses possess complex adaptability to local environments. The aim of VIR’s collecting mission to Voronezh and Tambov Provinces in 2016 was to replenish the preserved genetic diversity of leguminous and perennial forage crops with samples of interest for breeding for fodder and seed productivity and resistance to limiting environmental factors. The task of the collecting mission was to explore the territory and collect seeds of wild perennial forage and leguminous plants. The exploration route and collecting sites are indicated on the map. Geographical coordinates and descriptions of habitats were recorded for 38 collecting sites. During the survey of fourteen districts in Voronezh Province and two districts in Tambov Province, 169 plant samples were collected, including 140 forage plant accessions (33 species) and 29 leguminous ones (9 species). The most frequently occurring species were identified: Poa pratensis L., Melilotus officinalis (L.) Pall., Medicago falcata L., Vicia angustifolia L. and Lathyrus tuberosus L. Plants of Onobrychis arenaria (Kit.) DC. occur throughout Voronezh Province in meadow-steppe communities. Of interest are the samples of Agropyron pectinatum (Bieb.) Beauv. collected on the northern border of its area of distribution; three species of lower-growing fescue (Festuca rubra L., F. valesiaca Gaudin. and F. pseudovina Hack. ex Wiesb.); a perennial form of Medicago lupulina L.; a sample of Lotus corniculatus L. found on chalky outcrops of the Kalach Hills; red (Trifolium pratense L.), golden (T. aureum Pollich.) and strawberry (T. fragiferum L.) clovers from the valley of the Khoper River; pisiform vetch (Vicia pisiformis L.) from Kalach District and hairy vetch (V. villosa Roth) from Povorino District of Voronezh Province. The materials collected by the team were added to the holdings of VIR and are available for further study and use in breeding.